Doing Identity Work and Risky Endeavors? A Qualitative Research Synthesis of Predominantly White, Middle-Class Parents' Decision Making in the Context of Urban School Choice. Issue 1 (January 2019) - Ellison, Scott; Aloe, Ariel M.
The inversion hypothesis popularized by Ehrenhalt posits that recent urban migration trends in the United States constitute a reversal of the late 20th-century model of middle-class White flight to the suburbs and an urban core inhabited by a mostly working-class, minority population. The hypothesized blurring of the urban–suburban divide has led to calls that policymakers must seize the opportunity to foster racially and economically diverse urban schools before the inversion process is complete with the assumption that doing so will lead to more equitable educational opportunities. The aim of this study is to gain insight into the possibility of fostering racially and economically integrated urban schools in the context of school choice through a qualitative research synthesis of the decision making processes of predominantly White, middle-class families in the urban core as they make school choices. Findings from this research indicate that the decision making of parents in the studies sampled for this synthesis are bound up with their identity work as "city people"; that parents who go "against the grain" in choosing an urban public school perceive that choice to be a risky decision; and that those risks are mitigated by their access to cultural, social, and economic capital.